Efficacy Of Indigenous Arbuscular Mycorrhizal Fungi And Liquid Organic Fertilizer For Promoting The Vegetative Growth Of Soybean Plants (Glycine max L.) On Ultisols - Herdy Suparmanto; Husna Faad; Halim (Publisher Cv. Inara, 2020)
Utilization of ultisols in Southeast Sulawesi may be approached by inoculating viable arbuscular mycorrhizal fungi (AMF) exposing plant growth-promoting activities to the growth of native economical plants. This study investigated a combination of AMF and liquid organic fertilizers from coconut husks to improve the growth of soybean plants grown on ultisols as one of the potential marginal soils in the region. The coconut husk served as an abundant, cheap, yet potential source for the preparation of liquid organic fertilizers. This study used two factorial design with four treatment levels. The first factor was designed for different AMF species (10 g/pots): control (M0), Acaulospora delicata (M1), Septoglomus constrictum (M2), and Claroideoglomus etunicatum (M3) while the second factor was designed for different concentration of liquid organic fertilizer (mL/pots): control (P0), 150 mL/pots (P1), 200 mL/pots (P2), and 250 mL/pots (P3). Based on ANOVA results, the independent application of AMF species and liquid organic fertilizers gave significant results in regards to the experimental variables such as plant height, number of leaves, leaf area, and stem diameter. The best combination of treatment was observed in the treatment using Septoglomus constrictum with the concentration of liquid organic fertilizer of 250 mL (M2P3) to yield the highest growth performance of soybean plants on ultisols.